Optimizing coordinated control of distributed energy storage system in microgrid to improve battery life. (September 2020) - Ali, Asfand Yar; Basit, Abdul; Ahmad, Tanvir; Qamar, Affaq; Iqbal, Javed
Abstract: Microgrids based on renewable energy require energy storage systems to mitigate the power imbalances that arise due to variable and intermittent nature of renewable sources. Battery energy storage system (BESS) has been widely used to provide the necessary support. However, higher cost and limited life depending on number of charging and discharging cycles, restricts its application. The calendar life of the BESS can be improved by optimizing the control operation of the battery. This paper presents a control strategy for distributed BESS in a centrally controlled microgrid to enhance the calendar life of BESS. The proposed strategy controls the charging and discharging of individual batteries based on state of charge (SOC), state of health (SOH) and maximum capacity. The controller selects the BESS with better health and higher capacity for operation on priority resulting in better calendar life of the energy storage system. The simulations results for the test system indicates an overall improvement in calendar life of BESS by 57%.